Can price discrimination lead to product differentiation? A vertical differentiation model - Fabian Herweg (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
In this paper, I compare two-part tariff competition to linear pricing in a vertically differentiated duopoly. Consumers have identical tastes for quality but differ in their preferences for quantity. The main finding is that quality differentiation occurs in equilibrium if and only if two-part tariffs are permitted. Furthermore, two-part tariff competition encourages entry, which in turn increases welfare. Nevertheless, two-part tariff competition decreases consumers' surplus compared to linear pricing.
Keywords: L13; L11; D43; 330; Duopoly; Two-part tariff; Vertical differentiation; Preisdifferenzierung; Produktdifferenzierung; Produktqualität; Duopol; Wohlfahrtseffekt; Theorie